Methicillin-Resistant Staphylococcus aureus Colonization in Schoolteachers in Ontario - Beth A Hanselman; Steven A Kruth; Joyce Rousseau; J Scott Weese (Canadian Journal of Infectious Diseases and Medical Microbiology, 2008)
A prospective study of methicillin-resistant Staphylococcus aureus (MRSA) colonization was performed involving teachers at a science teachers’ conference in Toronto, Ontario. Nasal swabs and questionnaire data were collected from consenting individuals. MRSA colonization was identified in seven of 220 (3.2%) participants. No colonized individuals reported recent contact with the health care system, antimicrobial therapy, residence with health care workers or previous MRSA infections. Methicillin-susceptible S aureus colonization was identified in 72 of 220 (33%) individuals. The prevalence of MRSA colonization was higher than expected for a purportedly low-risk population.